B-mode and Doppler Ultrasonographic Assessment of Uterine Involution in Ewes Treated with Two Different Doses of ProstaglandinF2α - Evkuran Dal, Gamze; Enginler, Sinem Ozlem; Cetin, Ali Can; Baykal, Kerem; Sabuncu, Ahmet (Acta Scientiae Veterinariae, 2020)
Background: Several studies consisted of postmortem evaluations and B-mode ultrasonography have been performed on ovine uterine involution. However, researches with Doppler ultrasonography are very limited in ewes. Doppler ultrasonography is a non-invasive method which provides information about vascular dynamics of the tissues which cannot be examined by B-mode ultrasonography. The aim of the study was to evaluate the effects of two different PGF2α doses on uterine measurements by real time B-mode ultrasonography; and on uterine artery hemodynamics by pulsed-wave Doppler analysis during postpartum uterine involution in ewes. Materials, Methods & Results: The study was conducted with 30 primiparous Kiwircik ewes which lambed singleton without any complication. The ewes were randomly divided into three groups (n= 10 for each group). A single i.m. injection of 125 μg/sheep PGF2α, 75 μg/sheep PGF2α, and 1.0 mL/sheep sterile saline solution were administered to Group 1, 2, and 3, respectively. The day of parturition was considered as the first day of the study. Examinations were performed on days 1, 2, 3, 7, 14, 21 and 28. Diameters of previously gravid horn and caruncles were measured by real time B-mod ultrasonography. Presence of lochia was also noted. Uterine artery pulsatility index (PI), resistance index (RI), systolic/diastolic ratio (S/D) values were measured by pulsed-wave Doppler ultrasonography. The one-way analysis of variance and Duncan’s test were used for statistical analysis. The mean previously gravid horn diameters of ewes were 8.30 ± 0.16 cm and 1.53 ± 0.07 cm on day 1 and day 28, respectively. Previously gravid horn and caruncle diameters had a similar declining pattern in all groups as involution period proceeded. Involution was mostly completed by day 21. More than 50% reduction in uterine size was achieved in prostaglandin administered groups by day 7. Caruncles were not able to be identified after the second week postpartum. Lochia was observed for a longer period in control group. Uterine artery PI and RI showed fluctuations throughout involution period with a similar pattern among groups. S/D values progressively increased until day 14, then showed a decreasing pattern. Discussion: The effects of different PGF2α doses on uterine measurements and uterine artery hemodynamics during postpartum period were compared in ewes for the first time. The uterine size reduction in prostaglandin administered groups suggested that both PGF2α doses were effective in uterine involution. The last observation of lochia in uterine cavity were achieved by day 7 in prostaglandin administered groups, suggesting both PGF2α doses trigger uterine contractions which lead to the removal of uterine content. Automatic measurements by Doppler device were taken in order to provide uniformity and to prevent operator-based bias. The significantly higher uterine artery PI value found in Group 1 on day 1 might suggest the stimulatory effect of PGF2α administration on uterine contractility synergitically with already released endogenous PGF2α. Uterine artery PI and RI showed fluctuations throughout involution period and reached their peak values on day 14. The increasing S/D values up to day 14 indicated increasing diastolic flow, increasing resistance and decreasing blood perfusion in prostaglandin administered groups. Prostaglandin administered groups tended to show higher hemodynamic parameters throughout the study which suggested a vasoconstrictor effect of PGF2α. In conclusion, PGF2α administration on the day of parturition might have constrictor effects both on uterine artery and myometrium which leads to a reduction in uterine blood flow and a rapid decline in uterine size especially during early puerperium even with a reduced dose.